The Effect of Carotid Chemoreceptor Inhibition on Exercise Tolerance in Chronic Heart Failure - Collins, Sophie É.; Phillips, Devin B.; McMurtry, M. Sean; Bryan, Tracey L.; Paterson, D. Ian; Wong, Eric; Ezekowitz, Justin A.; Forhan, Mary A.; Stickland, Michael K. (Frontiers in Physiology, 2020)
Purpose: Chronic heart failure (CHF) is characterized by heightened sympathetic nervous activity, carotid chemoreceptor (CC) sensitivity, marked exercise intolerance and an exaggerated ventilatory response to exercise. The purpose of this study was to determine the effect of CC inhibition on exercise cardiovascular and ventilatory function, and exercise tolerance in health and CHF. Methods: Twelve clinically stable, optimally treated patients with CHF (mean ejection fraction: 43 ± 2.5%) and 12 age- and sex-matched healthy controls were recruited. Participants completed two time-to-symptom-limitation (TLIM) constant load cycling exercise tests at 75% peak power output with either intravenous saline or low-dose dopamine (2μg·kg-1·min-1; order randomized). Ventilation was measured using expired gas data and operating lung volume data were determined during exercise by inspiratory capacity maneuvers. Cardiac output was estimated using impedance cardiography, and vascular conductance was calculated as cardiac output/mean arterial pressure. Results: There was no change in TLIM in either group with dopamine (CHF: saline 13.1 ± 2.4 vs dopamine 13.5 ± 1.6 min, p=0.78; Control: saline 10.3 ± 1.2 vs dopamine 11.5 ± 1.3 min, p=0.16). In CHF patients, dopamine increased cardiac output (p=0.03), vascular conductance (p=0.01) and oxygen delivery (p=0.04) at TLIM, while ventilatory parameters were unaffected (p=0.76). In controls, dopamine improved vascular conductance at TLIM (p=0.03), but no other effects were observed. Conclusion: Our findings suggest that the CC contributes to cardiovascular regulation during full-body exercise in patients with CHF; however, CC inhibition does not improve exercise tolerance.